Assessment of potential biomarkers of subclinical vitamin K deficiency in patients with end-stage kidney disease. - Elliott, Meghan J.; Booth, Sarah L.; Hopman, Wilma M.; Holden, Rachel M. (2016)
Background Contexte: A significant proportion of hemodialysis patients have functional, but modifiable, vitamin K deficiency. Une proportion considérable de patients traités en hémodialyse ont une carence fonctionnelle, bien que modifiable, en vitamine K. L'objectif de cette étude est de déterminer la corrélation entre une carence en vitamine K chez les patients en hémodialyse.; Keywords: Chronic kidney disease, Hemodialysis, Phylloquinone, PIVKA, Osteocalcin, Vitamin K.; Springer Open.